PENGARUH MACAM PENGOLAHAN TANAH DAN DOSIS KALIUM TERHADAP TANAMAN JAGUNG MANIS (Zea mays saccharata Sturt.) PADA TANAH SUBSOIL ULTISOL - Saputtra, Ari Andika; Saputra, Ari Andika; Anwar, Risvan; Suzanna, Eka (Jurnal Agroqua: Media Informasi Agronomi dan Budidaya Perairan, 2024)
This research aims to determine the effect of types of soil processing and potassium dosage on the growth and yield of sweet corn plants in ultisol subsoil soil. The experiment used a Split Plot Design with 3 replications. The main plot is a type of land cultivation consisting of 3 levels, namely: no tillage, minimum tillage, maximum tillage. As a subplot, the dose of potassium fertilizer consists of 4 levels, namely: without fertilizer (control), dose 75 kg/ha, dose 150 kg/ha, and dose 225 kg/ha. The research data was analyzed using Diversity Analysis to find out whether the treatment had a real effect or an insignificant effect. If the results of the analysis have a real or very real effect, then continue with the Duncant's Multiple Range Test (DMRT) at the 5% level.This research concluded that: maximum tillage had a significant effect on plant height at 8 wap, number of leaves in the flowering phase, and ear circumference, and was very significant on leaf width, weight of husked cobs per plant, and weight of husked cobs per sweet corn plant planted in ultisol sub soil. The dose of potassium fertilizer of 225 kg/ha had a real and very significant effect on the variables of plant height at 4 wap, 6 wap, 8 wap, weight of cobs with husks and weight of cobs without husks. gave plant heights of 4 wap, 6 wap, 8 wap, highest cob weight with husks and cob weight without husks in sweet corn planted in Ultisol subsoil soil. The interaction of the type of soil processing and potassium dose influences the weight of cobs with husks per plant and the weight of cobs without husks per plant. The maximum type of tillage and a potassium dosage of 225 kg/ha provide the highest weight of husk-free cobs per plant and the highest weight of husk-free cobs per plant.